A Diagnostic Profile as a Tool in Research on Company Innovation - Romanowska, Maria (Studia Oeconomica Posnaniensia, 2017)
The aim of the article is to contrast the approach to research on innovation applied in economics with that applied in management. The author points to the need to adjust the research methods applied by business management researchers to the specific requirements of management as a scientific discipline.